Diving into the deep: fungal diversity in the newly discovered hydrothermal vents of Hatiba Mons, Red Sea - Schultz, Júnia; Altalhi, Sharifah; Zwan, Froukje M. van der; Augustin, Nico; Rosado, Alexandre Soares (Frontiers in Marine Science, 2025)
IntroductionHydrothermal vents are among Earth’s most extreme ecosystems, characterized by high temperatures, elevated metal concentrations, and steep chemical gradients that sustain specialized microbial life. Although bacterial and archaeal communities in these environments have been extensively studied, fungal diversity remains poorly understood. The recently discovered Hatiba Mons hydrothermal vent field in the Red Sea Rift provides a unique setting to investigate fungal communities in a hypersaline, metal-rich environment.MethodsWe analyzed fungal diversity in crusts, sediments, and microbial mats collected from five active vent sites at Hatiba Mons. A total of 38 subsamples were obtained using a remotely operated vehicle (ROV) during the KRSE Aegaeo RV cruise in May 2022. DNA was extracted, and the fungal ITS rRNA gene region was sequenced on an Illumina MiSeq platform. Sequence processing and taxonomic assignment were performed with QIIME2 and the UNITE database, while downstream statistical analyses were conducted in R with phyloseq.ResultsFungal community composition varied significantly across sample types, as shown by Principal Coordinates Analysis (PCoA) and confirmed by PERMANOVA. Ascomycota, Basidiomycota, and Chytridiomycota dominated the assemblages. Functional predictions using FUNGuild revealed diverse ecological roles, including saprotrophic, symbiotic, and pathogenic lifestyles.DiscussionThis study provides the first characterization of fungal communities in the Hatiba Mons hydrothermal system. The distinct taxonomic and functional profiles observed suggest that fungi contribute to biogeochemical cycling and ecosystem dynamics in extreme marine habitats. These findings expand current knowledge of fungal ecology in hydrothermal vents and underscore the importance of including fungi in future deep-sea microbiological research.